Prognostic impact of the number of resected lymph node on survival in colorectal cancer - Ladeira, Katia M. (2016)
Introduction Colorectal Cancer (CRC) is the third most common cancer and the second leading cause of death in Western countries. In Portugal, in the North, emerges as the second most common cancer. The presence of lymph node metastasis is an important predictor of overall and disease-free survival and several studies recommend the evaluation of at least 12–14 regional lymph nodes, as it contributes to improve cancer staging and patient outcomes. Aims Epidemiological characterization of the studied population and identify a possible relationship between the number of lymph nodes evaluated in the surgical specimen and survival. Methods We preceded to the study of 1065 CCR patients, submitted to surgical resection between 1 January 2000 and 31 August 2012, in Braga Hospital. Discussion/Conclusion The results of the epidemiological characterization of this population are coincident with those described in the literature. It was observed a significant correlation between age, tumor size, serosal invasion, differentiation, tumor penetration, venous and lymphatic invasion, metastasis, TNM stage and the number of lymph nodes evaluated. However, we did not observe a statistically significant correlation between patient survival and number of lymph nodes evaluated (p > 0.05). A possible explanation is the practice of oncologists, addressing patients with less than 12 nodes identified in the surgical specimen as “N-positive” and undergoing adjuvant therapy. A better harvest and careful analysis of lymph nodes would lead to more accurate staging, avoiding overtreatment and side effects associated, and allow better economic management of hospital resources, in real N0 patients. Npatients. patients. patients.